Strong Raman yield enhancement in large Si nanocrystals from ultraviolet to infrared: Density and shape dependence. (18th February 2019) - Faraci, Giuseppe; Italia, Markus; Ruggeri, Rosa; Litrico, Grazia; Mannino, Giovanni
Abstract: Silicon nanocrystals, few hundred nanometers in size, demonstrate impressive Raman yield enhancement. We report, first, the enormous Raman yield enhancement obtained with octahedral‐shaped nanocrystals in a wide wavelength range going from the ultraviolet, through the visible, to the infrared. We observed, along with the main Si peak amplification at 521 cm −1, also the amplification of the 480 cm −1 broad peak of a thin amorphous Si layer embedded between the nanocrystals, together with an amplification of the overall background under both Raman peaks. In order to clarify the mechanism governing the previous enhancements, the previous data were completed exploring the influence of shape by using irregular nanocrystals of similar size. These latter nanocrystals showed an amplified Raman yield, although reduced with respect to those of octahedral shape. Collected data, displayed as a function of the size and density, have been interpreted and discussed. Abstract : Enormous Raman yield amplification was observed with Si octahedral nanocrystals, in ultraviolet, visible, and infrared frequencies. Irregular nanocrystals of similar size show a lower Raman enhancement. These effects are attributed to magnified scattering inside and outside the nanocrystal, interparticle interaction, and shape‐dependent reflections.